2020
DOI: 10.1590/0004-282x20200065
|View full text |Cite
|
Sign up to set email alerts
|

Dietary habits in a group of patients with multiple sclerosis are similar to those of healthy control subjects

Abstract: Background: Multiple sclerosis (MS) is a chronic autoimmune disease of the central nervous system. Over time, patients with MS accumulate neurological disabilities. MS typically affects young adults and is associated with an inflammatory profile of cytokines and lymphocytes. If a patient were to consume a potentially inflammatory diet, it is possible that the evolution of MS in that individual would be more aggressive. Objective: To investigate whether patients with MS living in and around the city of Santo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
2
0
1
Order By: Relevance
“…We found no significant differences in MeDi adequacy between PwMS and HC, in line with previous findings ( 25 ). However, although most of the participants in both groups were sufficiently adherent to MeDi, a very low percentage of participants were completely adherent to it (2% PwMS and 1% HC).…”
Section: Discussionsupporting
confidence: 93%
“…We found no significant differences in MeDi adequacy between PwMS and HC, in line with previous findings ( 25 ). However, although most of the participants in both groups were sufficiently adherent to MeDi, a very low percentage of participants were completely adherent to it (2% PwMS and 1% HC).…”
Section: Discussionsupporting
confidence: 93%
“…No references were done to the adequacy of their intakes to the US recommendation. Another study ( 30 ), reported no remarkable differences in dietary habits between 34 healthy control subjects and 66 pwMS, except for higher consumption of carbohydrates in patients. When compared to the World Health Organization's recommended daily amounts, both groups had higher protein and lower carbohydrate intakes.…”
Section: Discussionmentioning
confidence: 92%
“…Diet in MS can be assessed via many instruments, such as the Dietary Questionnaire for Epidemiological Studies [ 7 ], food diaries, and shorter measures such as the Short‐Form Food Frequency Questionnaire [ 8 ] and the Diet Habits Questionnaire (DHQ) [ 9 ], used in the present study. Multiple studies have identified associations between diet and MS risk [ 10 , 11 ] disability [ 12 ], fatigue [ 12 , 13 , 14 ], and depression [ 12 , 15 ]; others have found no associations [ 14 , 15 , 16 , 17 , 18 ]. Our group has evaluated the cross‐sectional relationships of diet and disability [ 19 , 20 ], depression [ 21 ], and fatigue [ 22 ] at baseline using the Health Outcomes and Lifestyle In a Sample of people with Multiple sclerosis (HOLISM) cohort, finding that a higher DHQ score was associated with better outcomes.…”
Section: Introductionmentioning
confidence: 99%